Islam, Identitas dan Minoritas di Asia Tenggara - Ahmad Suaedy (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2010)
Globalization has encouraged the emergence of a challenge to respect minority rights are stronger in almost all countries are plural. The appearance was not only urged the governments in many countries to change their vision of nationalism, it even challenged the great narratives such as Islam, democracy and human rights to change the doctrine of justice that are not conventional. For that Islam, democracy and human rights alike are facing a change that can no longer be seen with the measures and standardization of the old uniform. This paper raised the challenge of empirical findings in Southeast Asia by taking samples of Malaysia, Thailand, and Philippines.